2017
DOI: 10.1007/s11136-017-1624-3
|View full text |Cite
|
Sign up to set email alerts
|

Item usage in a multidimensional computerized adaptive test (MCAT) measuring health-related quality of life

Abstract: PurposeExamining item usage is an important step in evaluating the performance of a computerized adaptive test (CAT). We study item usage for a newly developed multidimensional CAT which draws items from three PROMIS domains, as well as a disease-specific one.MethodsThe multidimensional item bank used in the current study contained 194 items from four domains: the PROMIS domains fatigue, physical function, and ability to participate in social roles and activities, and a disease-specific domain (the COPD-SIB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…The first studies comparing MCAT with UCAT performance focused on measuring ability; these studies showed that fixed-length MCATs were 25% to 33% shorter and resulted in more accurate ability estimates (Li & Schafer, 2005; Luecht, 1996; Segall, 1996). A recent study comparing MCAT with UCAT in the context of health measurement showed that MCATs were, on average, 20% to 25% shorter compared with using separate UCATs (Paap, Kroeze, Glas, et al, 2017). Although it may be tempting, it is difficult to compare these figures across studies directly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first studies comparing MCAT with UCAT performance focused on measuring ability; these studies showed that fixed-length MCATs were 25% to 33% shorter and resulted in more accurate ability estimates (Li & Schafer, 2005; Luecht, 1996; Segall, 1996). A recent study comparing MCAT with UCAT in the context of health measurement showed that MCATs were, on average, 20% to 25% shorter compared with using separate UCATs (Paap, Kroeze, Glas, et al, 2017). Although it may be tempting, it is difficult to compare these figures across studies directly.…”
Section: Discussionmentioning
confidence: 99%
“…This was not entirely surprising, given the dichotomous nature of the items. When it comes to polytomous items, previous studies have shown that item banks as small as 20 to 30 items per dimension may be adequate in supporting CAT when exposure control is not an issue (Boyd, Dodd, & Choi, 2010; Dodd, De Ayala, & Koch, 1995; Paap, Kroeze, Terwee, van der Palen, & Veldkamp, 2017). Overall, this study showed support for these findings, but it also allowed for refinement: Feasibility in the HEPO scenario was dependent on the observed θ-score pattern (for banks with 30 items or fewer per dimension).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After investigating a large number of studies, the above two models were not only commonly used polytomously scoring models in IRT, but also commonly used in CAT (e.g. Paap, Kroeze, Terwee, Palen, & Veldkamp, 2017). Therefore, the model with the smaller test-fit indices between the GRM and the GPCM was selected for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore the presented item bank should be large enough to support adequate measurement precision for all relevant levels of the latent construct one wishes to assess in the given application [ 48 , 49 ]. Past studies suggest that item banks as small as 20–30 polytomous items per dimension may be adequate when exposure control is not an issue [ 50 , 51 ]. A recent study [ 45 ] found that the required item bank size depended on adequate targeting (the match between the item bank and the latent trait distribution).…”
Section: Efficiency and Precision Of An Item Bankmentioning
confidence: 99%